Implementation Of Intrusion Detection System (Ids) Using Security Onion - Rulof Baltwin Tallane; Dian Widiyanto Chandra (Syntax Corporation, 2022)
Intrusion Detection System (IDS) is a system in charge of monitoring network traffic to detect suspicious and abnormal activity and provide alerts when such activity is detected. The use of the Intrusion Detection System is very helpful for administrators to monitor network traffic so as to minimize the occurrence of attacks that result in system damage and data theft. To minimize the occurrence of system damage and data theft by attackers, the author implements an Intrusion Detection System using Security Onion so that when an attack occurs it can be directly handled by the administrator. In this study, a test was conducted on Security Onion using the Signature Based method in detecting Remote Access Trojan attacks which according to BSSN data from January to April 2020 were the most common types of attacks. The results of this study can be used to detect cyber attacks that result in system damage and data theft.